Biomass equipment suppliers and technological potential in selected Philippine Agro-based Industries. - Dalusung, Alberto R. III (Philippine Engineering Journal)
This paper gives an overview of the technical and financial viability of using agricultural residues to generate heat and/or electricity. The government's policy toward cogeneration and private sector power generation is discussed. The paper identifies the key factors that boost the potential of cogeneration, particularly when available biomass residues such as bagasse, rice husk and coconut shells/husks are used. It also looks at the technical, economic/financial and institutional issues that confront projects of this nature. The paper discusses the status of domestic manufacturing capability and the end-user interest in cogeneration projects. Finally, it gives a profile of three sectors (namely sugar, rice and coconut) with potential for the application of cogeneration projects using biomass residues.